EVALUASI MULTIDIMENSI PSIKOLOGI LINGKUNGAN PADA CO-WORKING SPACE AKADEMIK DI SGLC UGM - Aliya Jauhari Hildayanti; Nedyomukti Imam Syafii (Jurnal Arsitektur ARCADE, 2026)
Abstract: Research on co-working spaces has predominantly focused on commercial settings, while studies employing an environmental psychology approach in academic co-working spaces in Indonesia remain limited. This study aims to evaluate user satisfaction in the co-working spaces of the Smart Green Learning Center (SGLC), Universitas Gadjah Mada, based on environmental psychology dimensions. A quantitative-descriptive approach was employed involving 240 respondents across 25 co-working space units. Data were collected through a questionnaire covering environmental control, thermal comfort, visual comfort, acoustics and privacy, spatial flexibility, and social perception. Data were analyzed using descriptive statistics and supported by users’ open-ended responses. The results indicate that overall user satisfaction was very high, with a mean score of 4.26. Spatial flexibility achieved the highest score (4.37), followed by visual comfort (4.22) and social perception (4.20), while acoustics and privacy received the lowest score (3.57). In addition, 26.3% of respondents reported experiencing thermal discomfort while using the spaces. These findings suggest that the quality of user experience in academic co-working spaces is influenced by the interaction of physical, psychological, and social aspects of the environment. The study highlights the importance of an environmental psychology approach in the design and evaluation of collaborative learning spaces in higher education settings. Keyword: Environmental psychology, User satisfaction, Co-working space Abstrak: Penelitian mengenai co-working space umumnya berfokus pada konteks komersial, sedangkan kajian berbasis psikologi lingkungan pada co-working space akademik di Indonesia masih terbatas. Penelitian ini bertujuan mengevaluasi kepuasan pengguna co-working space di Smart Green Learning Center (SGLC) Universitas Gadjah Mada berdasarkan dimensi psikologi lingkungan. Penelitian menggunakan pendekatan kuantitatif-deskriptif dengan melibatkan 240 responden pada 25 unit co-working space. Data dikumpulkan melalui kuesioner yang mencakup dimensi environmental control, kenyamanan termal, kenyamanan visual, akustik dan privasi, fleksibilitas ruang, serta persepsi sosial. Analisis dilakukan menggunakan statistik deskriptif dan didukung oleh tanggapan terbuka pengguna. Hasil penelitian menunjukkan bahwa tingkat kepuasan pengguna tergolong sangat tinggi dengan nilai rata-rata 4,26. Fleksibilitas ruang memperoleh nilai tertinggi (4,37), diikuti kenyamanan visual (4,22) dan persepsi sosial (4,20), sedangkan akustik dan privasi memperoleh nilai terendah (3,57). Sebanyak 26,3% responden masih mengalami ketidaknyamanan termal selama menggunakan ruang. Temuan ini menunjukkan bahwa kualitas pengalaman pengguna co-working space akademik dipengaruhi oleh interaksi aspek fisik, psikologis, dan sosial dalam lingkungan ruang. Hasil penelitian menegaskan pentingnya pendekatan psikologi lingkungan dalam perancangan dan evaluasi ruang belajar kolaboratif pada lingkungan pendidikan tinggi. Kata Kunci: Psikologi lingkungan, Kepuasan pengguna, Co-working space